Development and evaluation of an online, patient-driven, family outreach intervention to facilitate sharing of genetic risk information in families with Lynch syndrome. Issue 6 (18th May 2021) - Pande, Mala; Peterson, Susan; Lynch, Patrick M
Abstract : Background: Identifying at-risk relatives of individuals with genetic conditions facilitates 'cascade' genetic testing and cancer prevention. Although current standards of care give mutation-positive (index) patients the responsibility of sharing genetic risk information with relatives, the communication is suboptimal, limited largely to close relatives. We developed FamilyCONNECT, a provider-mediated, patient-navigated online tool to facilitate family outreach, and assessed its feasibility, usability and acceptability. Methods: (1) Development of the FamilyCONNECT prototype; (2) testing using online surveys of: (a) members of Lynch Syndrome (LS) International (LSI); (b) genetics service providers; and (3) hands-on testing with patients with LS. Results: (1) FamilyCONNECT's features include introductory email to elicit participation, informational website/video, identity authentication/account creation, informed consent, sharing of genetic test results, pedigree expansion and process to invite at-risk relatives. (2a) 33% of the 170 LSI participants completed the survey. FamilyCONNECT's features received favourable responses from at least 79% of respondents. Unfavourable responses were for length of the consent document and mistrust of opening emailed links. (2b) Thirty-five genetics professionals responded to the providers' survey. Key perceived barriers to FamilyCONNECT's usage were privacy/confidentiality (83%), a lack of institutional resources (76%), a defined process (66%) and time (69%). (3) Ten patients navigated data collection fields and provided feedback for improvements. Conclusion: FamilyCONNECT tool's content and features were well received among patients with LS as well as providers. The tool could be a viable alternative to increase family outreach among patients with LS. Future efforts will focus on refining FamilyCONNECT and assessing its uptake and utilisation by patients with LS.